A Comprehensive Study of the Android and Mobile Industry with Proposed Future Aspects (International Journal of Food and Nutritional Sciences, 2022)
Comprehensive survey of the various versions of the Android operating system, tracing its evolution from its initial release to the latest version. Android, as the most widely used mobile operating system globally, has undergone significant transformations, with each version introducing new features, enhancements, and improvements that have shaped the mobile computing landscape. This study explores the chronological development of Android, examining key milestones, major updates, and the impact of each version on user experience, security, and app development. Through a detailed analysis of the changes in user interface (UI), performance optimizations, and security enhancements, this paper highlights the progressive refinement of the Android platform. Additionally, discusses the challenges posed by version fragmentation and considers the implications of these developments for future iterations of the operating system. The findings of this survey provide valuable insights into the Android ecosystem’s evolution, offering a detailed reference for researchers, developers, and enthusiasts interested in mobile operating systems.